QUALITY OF SMOKE-FLAVORED CATFISH (Pangasius hypophthalmus) FILLET PREPARED FROM DIFFERENT SIZES OF FISH - Malau, Chandra Yustitia; Hasan, Bustari; Leksono, Tjipto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACt The aim of this study was to evaluate the effect of different whole fish sizes on quality of smoke-flavored fish. Three groups of whole fish, 500, 750 and 1000 gram in size were flavored in 6% liquid smoke for 1 hours, and dried in oven at 60oC for 4-5 hours. Smoke-flavored fillets were analyzed for product yield, proximate and amino acid composition, phenol, acidity and sensory quality. The results showed that the smoke-flavored fillets prepared from whole fish of 500 gram in weight were the best in quality, which characterized by product yield 33,16%, moisture 10.53%, ash 5.28%, protein 56.61%, fat 5.28%, total acidity 2.24%, phenols 64.5%, and complete amino acid profile. The smoke-flavored fillets have characteristics as very neat, less greasy, less moist, less brownish yellow in colour, suffescient smoke odor, no additional disturbing taste, solid, compact and dry. Therefore, whole fish having 500 gram in size (190 gram fresh fillet) was recommended for smoke-flavored fillet. Keywords: smoke-flavored fillets, whole fish size, proximate,phenol, sensori quality